Sanctioning to change state behaviour - Niccolò Ridi; Veronika Fikfak (University of Hamburg, Institute of Law and Economics (ILE), 2022)
[Conclusion:] In this article we have sought to address sanctioning not just as a notion, but as a complex and multifaceted phenomenon which, rather than being a mere predicate of international law, unfolds within or notwithstanding it. We have done so with a view to unpacking the phenomenon at a structural level and showing the promise of the notion of sanctioning for the purpose of understanding the dynamics of state behaviour and compliance with international law obligations-and beyond. By employing a high-level, conceptual approach, we have sought to argue that, even within international law, a legalistic approach to the sanctioning phenomenon is inevitably reductive. Moreover, we submit that the concept maintains its utility and explanatory power as a lens through which several types of international interactions may be examined, and suggest that future research will develop and test the hypotheses set out in our contribution.
Keywords: 340